(untitled) (Nonconventional Technologies Review, 2024)
The paper deals with thermal analysis and the mode of heat dissipation on the surfaces of the 3D printer parts. The paper presents both the 3D modelling part of the components related to the E3D Volcano assembly, the realization of the simulation models using the necessary conditions for the heat transfer phenomenon, more precisely in the current study we will only use thermal convection and thermal radiation as well as the realization of a mathematical calculation regarding the thermal part using real values. Very important in this case are also the materials used for each part of the assembly because they play an important role in heat transfer regarding thermal conductivity. Also, in the final part of the paper, the simulation after the mathematical power calculation is proposed regarding the evolution of the temperature on the entire E3D Volcano assembly and the graphic representation of the diagram T [oC] according to the power of the resistance P [W].